First discovery of trans-iron elements in a DAO-type white dwarf (BD−22°3467). Issue 1 (20th November 2019) - Löbling, L; Maney, M A; Rauch, T; Quinet, P; Gamrath, S; Kruk, J W; Werner, K
ABSTRACT: We have identified 484 lines of the trans-iron elements (TIEs) Zn, Ga, Ge, Se, Br, Kr, Sr, Zr, Mo, In, Te, I, Xe, and Ba, for the first time in the ultraviolet spectrum of a DAO-type white dwarf (WD), namely BD−22°3467, surrounded by the ionized nebula Abell 35. Our TIE abundance determination shows extremely high overabundances of up to 5 dex – a similar effect is already known from hot, H-deficient (DO-type) WDs. In contrast to these where a pulse-driven convection zone has enriched the photosphere with TIEs during a final thermal pulse and radiative levitation has established the extreme TIE overabundances, here the extreme TIE overabundances are exclusively driven by radiative levitation on the initial stellar metallicity. The very low mass (0.533^+0.040_-0.025 M_ ) of BD−22°3467 implies that a third dredge-up with enrichment of s-process elements in the photosphere did not occur in the asymptotic giant branch (AGB) precursor.